PEMBUATAN GUIDANCE BOOK TENTANG ALUR KEGIATAN MAGANG DI KEMENTERIAN DESA, PEMBANGUNAN DAERAH TERTINGGAL DAN TRANSMIGRASI - Susanti, Risa; Hedian, Haniifa; Syuja, Dhia Nadhira; Ramadhan, Muhammad (Jurnal Serina Abdimas, 2023)
ABSTRACT Internship or work practice is a form of learning activity that provides insight and practical experience to students regarding real activities in the world of work. Because of the importance of internships for students and also the limited time given in carrying out internships or work practices. In order for internships to achieve their goals, it is important to provide guidance during internships so that internships can take place effectively. To ensure that the internship activities carried out by students run well, a guidebook is needed as a reference for students during the internship activity. The Ministry of Villages is one of the government agencies that does not yet have a guidebook on internship activities for interns. So that internship activities at the Ministry of Villages, Development of Disadvantaged Regions and Transmigration are less effective due to unclear information about internship activities. Seeing this, we as the PKM implementation team want to help and provide solutions for the relevant agencies. The intervention provided by the PKM implementation team was to make a guide book (guidance book) regarding the flow of internship activities at the Ministry of Villages to ensure that internship activities run well and regularly. The preparation of this guidebook was made by interviewing the ministry as well as theoretical studies or by gathering the resources needed in compiling the guidebook. ABSTRAK Magang atau praktik kerja adalah suatu bentuk kegiatan pembelajaran yang memberikan wawasan dan pengalaman praktis kepada mahasiswa mengenai kegiataan riil di dunia kerja. Karena pentingnya kegiatan magang untuk mahasiswa dan juga adanya keterbatasan waktu yang diberikan dalam melaksanakan kegiatan magang atau praktik kerja. Agar kegiatan magang dapat mencapai tujuan, pentingnya bimbingan selama menjalankan kegiatan magang sehingga kegiatan magang dapat berlangsung dengan secara efektif. Untuk memastikan kegiatan magang yang dilaksanakan oleh mahasiswa berjalan dengan baik, diperlukan buku panduan sebagai acuan untuk mahasiswa selama kegiatan magang berlangsung. Kementerian Desa adalah salah satu instansi pemerintahan yang belum memiliki buku panduan mengenai kegiatan magang untuk mahasiswa magang. Sehingga kegiatan magang di Kementerian Desa, Pembangunan Daerah Tertinggal dan Transmigrasi kurang efektif akibat informasi mengenai kegiatan magang yang kurang jelas. Melihat adanya hal ini, kami selaku tim pelaksana PKM ingin membantu dan memberikan solusi untuk instansi terkait. Intervensi yang diberikan oleh tim pelaksana PKM adalah membuat buku panduan (guidance book) mengenai alur kegiatan magang di Kementerian Desa untuk memastikan kegiatan magang berjalan dengan baik dan teratur. Pembuatan buku panduan ini dibuat dengan wawancara dengan pihak kementerian serta kajian teori atau dengan mengumpulkan sumber yang dibutuhkan dalam menyusun buku panduan.